If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6b + 6 = -48 Reorder the terms: 6 + 6b = -48 Solving 6 + 6b = -48 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6b = -48 + -6 Combine like terms: 6 + -6 = 0 0 + 6b = -48 + -6 6b = -48 + -6 Combine like terms: -48 + -6 = -54 6b = -54 Divide each side by '6'. b = -9 Simplifying b = -9
| -7+8n=5+13n | | 10-1235=21 | | -21x^2-20x-4=0 | | 2x^3-50x+72=0 | | 2+2+1+1+7+3+2+4+1+4= | | 4(x-1)=1.2(x-8) | | 9+10x=.4 | | x^3+x^2-18x-54=0 | | 9+10x=.2 | | 10-29v+10v^2=0 | | 10-1+4+(-16)= | | -9.2-x=4.5 | | 10z+4=2(5z+8) | | -18=-4y+6+2y | | -5(2-3x)=2(4x+1) | | 4b^3+9b^2+5b=0 | | 18-7x=20.5 | | 3x+38=9x+28 | | 5(x-7)+4=3(x-7) | | 3(2a-7)=-39 | | -5=2c+10 | | 21r^2+184r+75=0 | | 6-(3x-7)= | | 15=-3x+9 | | -2(7x-5)+1=-14x+11 | | x-.2x=69500 | | 4*+2=18 | | 2x(8-4+9+7)= | | 2(5x+2)-x= | | -43+5m=-73 | | -30+4m=-54 | | h^2+3h-28= |